2017
DOI: 10.18203/2394-6040.ijcmph20173815
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associate factors of low birth weight in North Indian babies: a rural based study

Abstract: Background: LBW is universally used as an indicator of health status and is an important subject of national concern and a focus of health policy. LBW is the strongest determinant of infant morbidity and mortality in India. Regional estimates of LBW include 28% in south Asia, 13% in sub-Saharan Africa and 9% in Latin America. Among regions, South Asia has the highest incidence of LBW; with one in four newborns has LBW. In 2011, Indian Statistical Institute reported nearly 20% of new born have LBW in India. DLH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
14
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 3 publications
(5 reference statements)
5
14
1
Order By: Relevance
“…104 (18.27%) newborns were low birth weight (LBW) and 465 (81.27%) were normal birth weight (NBW)( Table 2). The percentage of LBW corroborates with the prevalence of LBW in south Asia (20%) [28,29] . The percentage of LBW babies born to VDD mothers was 18.09%, which was very similar to the percentage of LBW babies born to VDS mothers (18.31%) (p = 0.76456749).…”
Section: Maternal Vitamin D Levelssupporting
confidence: 75%
“…104 (18.27%) newborns were low birth weight (LBW) and 465 (81.27%) were normal birth weight (NBW)( Table 2). The percentage of LBW corroborates with the prevalence of LBW in south Asia (20%) [28,29] . The percentage of LBW babies born to VDD mothers was 18.09%, which was very similar to the percentage of LBW babies born to VDS mothers (18.31%) (p = 0.76456749).…”
Section: Maternal Vitamin D Levelssupporting
confidence: 75%
“…22 Kumar et al in Haryana determined that sex of baby, type of family, socioeconomic status, maternal education and maternal occupation, were important risk factors leading to LBW. 8 Similarly Johnson also found statistically significant associations between birth weight and economic status, maternal pregnancy weight gain, number of ANC visits and maternal education. 9 The present study identified lower education status of mothers, multigravidity, inadequate ANC visits, preterm births and female sex as risk factors for LBW babies.…”
Section: Discussionmentioning
confidence: 88%
“…4 Similar studies conducted across India had nearly the same magnitude of prevalence of LBW ranging from 14% to 36%. [5][6][7][8][9] Metgud et al in a study in Karnataka, identified maternal illiteracy, exposure to passive smoking, maternal age, weight gain during pregnancy, high risk pregnancy and late antenatal registration as the risk factors significantly associated with the birth weight of a newborn. 7 Noor et al performed similar study in Madhya Pradesh and found that gestational age and parity were the important maternal parameters influencing the birth weight of the child.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of low birth weight as calculated by our study is 30% (45/150) which was similar to estimates of 28% in South east Asia but higher than DLHS 4 study conducted in 2011 by Statistical Institute of India which reported nearly 20% of new-born have low birth weight in India. 10 We found that mean age of mother was 27.6 years (95% CI, ±4.32). Out of 150 mothers enrolled, age of mother <20 year constituted 3.33% of study while 20-30 year age group formed 73.66% of group and >30 year aged mother formed 24% of total sample size.…”
Section: Discussionmentioning
confidence: 74%